Dampak Penerapan Sistem Pengendalian Internal untuk Pencegahan Kecurangan Akuntansi - Andi hidayatul Fadlilah; Eko Wiji Pamungkas; A. Ary Setyawan; Carolina Ety Widjayanti; Sari Mustika Widyastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The internal control system helps minimize the risk of accounting fraud. With strong internal controls, companies can implement procedures that limit access and responsibility in financial management. The purpose of this study was to analyze the effect of implementing an internal control system for preventing accounting fraud. The research method used is a literature study or Library Research with a qualitative approach. Based on the literature review conducted on the results and discussion, there is a conclusion that internal control plays an important role in preventing accounting fraud in an agency. Keywords: internal control, accounting fraud